Hacking Power Grids: A Current Problem. - Kshetri, Nir; Voas, Jeffrey (Computer (00189162), 2017)
Cyberattacks against power grids and other critical infrastructures are increasing in frequency and severity. Government and industry stakeholders must take more active steps to address the problem before a major catastrophe occurs.